Luis Cernuda y la canción tradicional - López Castro, Armando (Huarte de San Juan. Filología y Didáctica de la Lengua, 2000)
With this work "Las nubes" (1937-1940), Luis Cernuda starts his maturity period and consolidates his style, which does not show any change in his next works. The poet from Seville chooses the spontaneity of colloquial language, lacking rhetoric, which answers to the direct experience, lived through; thus, his thoughts are translated into rhythmic speech. Cernuda’s trend towards the poem-song form, also frequent in Lorca and Alberti’s writing, leads him not only to leave metric regularity and imitate the timeless incoherence but also to use the spoken language. These features prove the musical sense of his writing.